Measurement of mono ethylene glycol volume fraction at varying ionic strengths and temperatures - Al Helal, A.; Soames, A.; Gubner, Rolf; Iglauer, Stefan; Barifcani, Ahmed (Elsevier Inc., 2018)
The estimation of Mono Ethylene Glycol (MEG) concentration is an essential criterion during the industrial regeneration of MEG to evaluate the efficiency of regeneration process and to control the concentration of MEG reinjected at the wellhead. Although many laboratory methods to determine MEG concentration exist, their application may be costly in terms of the time required to perform sampling and laboratory analysis. For this reason, an alternative method for determination of MEG concentrations has been proposed. This method can be performed on-site utilizing physical properties that can be readily measured using portable measurement devices including refractive index (n D ), electrical conductivity (EC) and total dissolved solids (TDS). The volume fraction (F vm ), n D , EC, and TDS of MEG solutions have been measured at (283.15, 298.15, and 323.15) K, (10–100) vol. %, and at (0, 0.125, 0.25, 0.5, 1.0) M NaCl total volume of solution) ionic strength (IS). The experimental results were then correlated to develop a simplistic model capable of estimating the volume fraction of MEG mixtures at varying ionic strengths. The proposed models will therefore allow a quick and convenient method for the determination of MEG concentrations in the field to quickly identify undesirable changes in produced lean MEG concentration.